A comparative study on the efficacy of honey and ethanol as cytological fixatives - M., Sona; S., Preethamol (International Journal of Advances in Medicine, 2017)
Background: In cytological fixatives prior to Papanicolaou staining smears are fixed mostly in alcohol or any alcohol based special purpose fixative. Alcohols are costly, hazardous and also there is a problem of disposal. Here, a very cheap and easily available alternate for fixative was being used. The objective was to describe the efficacy of 20% honey as a cytological fixative in comparison to ethanol. Methods: The study was done on buccal smears from students of Department of MLT, Government Medical College, Thiruvananthapuram, Kerala, India for a period of six months after ethical approval. Two buccal smears were collected from either cheek using wooden spatula/blunt end of the Ayers spatula. One of the smear is fixed in ethanol (95%) and the other smear is fixed in honey (20%). The slides were scored based on the assessment parameters: nuclear staining, cytoplasmic staining, cell morphology, clarity of staining and uniformity of staining. Results: The study was done on buccal smears, the sample were smeared and fixed onto slides using two fixatives- 95% ethanol and 20% honey. Both reported good quality staining feature, preservation of morphology and a crisp nuclear and cytoplasmic staining. It has also added advantage of being nontoxic, economical, non-flammable, non-hazardous, no problems associated with license of purchase, reduces overall turnaround time and is easy to handle without any sort of irritation. Conclusions: Thus, the overall study shows that honey has got a fixative action, which can be implemented soon in the industry.